Emergent dynamics of scale-free interactions in fractional quantum Hall fluids - Yang, Bo (2024)
We show that even with arbitrarily large cyclotron gap, Landau level (LL) mixing can be dominant with scale-free interaction in a fractional quantum Hall system, as long as the filling factor exceeds certain critical values. Such scale-free interaction with kinetic energy can serve as exact model Hamiltonians for certain composite Fermion or parton states (unlike the well-known TK Hamiltonians where the number of LLs needs to be fixed by hand), and they are natural physical Hamiltonians for 2D systems embedded in higher-dimensional space time. Even with LL mixing the null spaces of such Hamiltonians (spanned by the ground state and the quasiholes) can be analytically obtained, and we show these are the generalization of the conformal Hilbert spaces (CHS) to more than one LLs. The effective interaction between the anyons for these topological phases emerges from the kinetic energy of the "elementary particles,"leading to an interesting duality between strongly and weakly interacting systems that can be easily understood via the tuning of parameters in the scale-free interaction. We also propose an experimental platform for approximately realizing such model Hamiltonians with trionlike particles that can potentially lead to very robust (non-Abelian) FQH phases from two-body Coulomb-based interaction.